A review on the catalytic ozonation of pollutants in wastewater by heteroelements-doped biochar: Internal and external doping strategies - Ruinan Zhao (Alexandria Engineering Journal)
Biochar has been widely developed for the remediation of water pollution, and how to improve the performance of biochar has attracted widespread attention. Heteroelements doping makes biochar have more active centers and durability in catalytic ozonation, which has great development prospects and has attracted the interest of researchers. This study reviews the application of heteroelements dope biochar in catalytic ozonation for wastewater treatment. First, the types of doping elements are discussed, and different doping methods and preparation methods are introduced in detail, among which external doping is widely used, and internal doping is cost-effective and easy to operate. Secondly, the application and mechanism of catalytic ozonation for the degradation of different pollutants are discussed. In addition, the economic costs of different doping methods are compared, and the challenges faced by heteroelements-doped biochar in catalytic ozonation in the future are proposed. This study provides a theoretical basis for the synthesis of low-cost and high-efficiency biochar catalysts for catalytic ozonation in real industrial wastewater treatment.